2015
DOI: 10.5505/tjtes.2015.63822
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Acute Effects of Hypericum Perforatum (Kantaron) Treatment in Experimental Thermal Burns and Comparison with Silver Sulfadiazine Treatment

Abstract: BACKGROUND: Hypericum perforatum (HP) (St. John's Wort-Kantaron) has been used widely for the treatment of burn injuries for many years in traditional Turkish medicine. The aim of study was to investigate HP treatment in experimental thermal burns and compare it with silver sulfadiazine (SS) treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…1 [62, 6570]; 2 [53, 7678, 138152]; 3 [66, 68, 93, 97, 98, 100, 153157]; 4 [158]; 5 [38, 93, 118, 119, 123–126, 157, 159–169]; 6 [170]; 7 [171]; 8 [172]; 9 [102, 103, 173]; 10 [174];; 11 [93]; 12 [93, 117–119]; 13 [167] 14 [65, 69, 175]; 15 [76, 79, 139–141, 151, 177, 178, 176, 179]; 16 [97]; 17 [120122]; 18 [68]; 19 [78, 138, 152, 170]; 20 [68, 102, 103]; 21 [160, 166, 180]; 22 [79, 149, 150]; 23 [168, 181]; 24 [82]; 25 [35, 37, 104]; 26 [182]; 27 [29, 5763]; 28 [31, 32, 82, 84, 87, 88, 183, 184]; 29 [104]; 30 [81]; 31 [185]; 32 [29, 64, 186]; 33 […”
Section: Resultsmentioning
confidence: 99%
“…1 [62, 6570]; 2 [53, 7678, 138152]; 3 [66, 68, 93, 97, 98, 100, 153157]; 4 [158]; 5 [38, 93, 118, 119, 123–126, 157, 159–169]; 6 [170]; 7 [171]; 8 [172]; 9 [102, 103, 173]; 10 [174];; 11 [93]; 12 [93, 117–119]; 13 [167] 14 [65, 69, 175]; 15 [76, 79, 139–141, 151, 177, 178, 176, 179]; 16 [97]; 17 [120122]; 18 [68]; 19 [78, 138, 152, 170]; 20 [68, 102, 103]; 21 [160, 166, 180]; 22 [79, 149, 150]; 23 [168, 181]; 24 [82]; 25 [35, 37, 104]; 26 [182]; 27 [29, 5763]; 28 [31, 32, 82, 84, 87, 88, 183, 184]; 29 [104]; 30 [81]; 31 [185]; 32 [29, 64, 186]; 33 […”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to increase vascularization during repair of connective tissue and damaged tissues (16). Kıyan et al conducted a study using rats with Hypericum perforatuminduced burn injuries (5). The investigators suggested that wound healing may be the result of fibroblast migration and stimulation of collagen synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Hypericum perforatum (HP) (St. John's Wort-Kantaron), widely for the treatment of burn injuries for many years in traditional Turkish medicine, was compared with silver sulfadiazine (SS) in the treatment of second-degree thermal burn created on the dorsal sites of rats. The measures of epidermal thickness and number of vessels demonstrated that HP administered four times a day within the first 24 h is clearly effective in wound healing in the experimental thermal second-degree burn and is significantly superior to SS treatment [105]. models showed remarkable wound-healing activity [106].…”
Section: Other Plant Species Used In Wound Healingmentioning
confidence: 98%